How to marry a cowboy ebook - Brown, Carolyn (Cowboys & Brides, 2014)
Book 4 of Cowboys & Brides From New York Times and USA Today-bestselling author Carolyn Brown comes a contemporary Western romance filled to the brim with sexy cowboys, gutsy heroines, and genuine down-home Texas twang. Texas rancher Mason Harper's daughters want a new mama in the worst way, and when a beautiful woman in a tattered wedding gown appears on their doorstep, the two little girls adopt her—no ifs, ands, or buts about it. Mason isn't sure about taking in a complete stranger, but Lord knows he needs a nanny, and Annie Rose Boudreau stirs his heart in long-forgotten ways... Annie Rose is desperate, and when a tall, sexy cowboy offers her a place to stay, she can't refuse. After all, it's just for a little while. As she settles in deeper, her heart tells her both Mason and her role as makeshift mama suit her just fine. But will Mason feel the same way once her nightmare past catches up with her? Fans of Linda Lael Miller and Diana Palmer will thrill to this moving story of a lonely cowboy and his two little girls finding the family of their dreams. Cowboys & Brides Series: Billion Dollar Cowboy (Book 1) The Cowboy's Christmas Baby (Book 2) The Cowboy's Mail Order Bride (Book 3) How to Marry a Cowboy (Book 4) Praise for Bestselling Contemporary Western Romances by Carolyn Brown: "Sizzling... Brown imbues her lively story with lots of heart."—Publishers Weekly "Hilarious...a great, entertaining read."—Fresh Fiction "Writing so expressive I could almost hear the country drawl."—Night Owl Reviewer Top Pick, 4 stars